Industry funded patient information and the slippery slope to New Zealand. Issue 7622 (4th October 2007) - Toop, Les; Mangin, Dee
Abstract : Industry funded health information campaigns could become common on our television screens if the European Commission proposals are passed. Les Toop and Dee Mangin warn that Europe could end up with similar problems to those in their country